Ocean heat storage in response to changing ocean circulation processes - Boeira Dias, FB; Fiedler, R; Marsland, SJ; Domingues, CM; Clement, L; Stephen Rintoul; Mcdonagh, EL; Mata, MM; Abhishek Savita (2020)
Ocean heat storage due to local addition of heat (“added”) and due to changes in heat transport (“redistributed”) were quantified in ocean-only 2xCO2 simulations. While added heat storage dominates globally, redistribution makes important regional contributions, especially in the tropics. Heat redistribution is dominated by circulation changes, summarized by the super-residual transport, with only minor effects from changes in vertical mixing. While previous studies emphasized the contribution of redistribution feedback at high latitudes, this study shows that redistribution of heat also accounts for 65% of heat storage at low latitudes and 25% in the midlatitude (35°–50°S) Southern Ocean. Tropical warming results from the interplay between increased stratification and equatorward heat transport by the subtropical gyres, which redistributes heat from the subtropics to lower latitudes. The Atlantic pattern is remarkably distinct from other basins, resulting in larger basin-average heat storage. Added heat storage is evenly distributed throughout midlatitude Southern Ocean and dominates the total storage. However, redistribution stores heat north of the Antarctic Circumpolar Current in the Atlantic and Indian sectors, having an important contribution to the peak of heat storage at 45°S. Southern Ocean redistribution results from intensified heat convergence in the subtropical front and reduced stratification in response to surface heat, freshwater, and momentum flux perturbations. These results highlight that the distribution of ocean heat storage reflects both passive uptake of heat and active redistribution of heat by changes in ocean circulation processes. The redistributed heat transport must therefore be better understood for accurate projection of changes in ocean heat uptake efficiency, ocean heat storage, and thermosteric sea level.